Soft (1,2)*-Omega Separation Axioms and Weak Soft (1,2)*-Omega Separation Axioms in Soft Bitopological Spaces - I. Mahmood, Sabiha; Adel Abdul-Hady, Asaad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In the present paper we introduce and study new classes of soft separation axioms in soft bitopological spaces, namely, soft (1,2)*-omega separation axioms and weak soft (1,2)*-omega separation axioms by using the concept of soft (1,2)*-omega open sets. The equivalent definitions and basic properties of these types of soft separation axioms also have been studied.